10 things to think about when building the perfect SOA why we're learning more about making SOAs work the first time. - Linthicum, David
Right now the implementation of SOAs seems involve much more hype than actual work. However, there are some patterns beginning to emerge, or, procedures the implementers are doing right to insure success. These patterns are not always obvious, so perhaps this is a good time to learn through the successes of others and do our own homework before we spend millions on moving to an SOA.